Islamic Images and Terminology Used in the Western Media - Quraishy, Bashy (Mediator, 2005)
Most societies in Western World has formulated a premature assumptions toward Islam due to the negative depictions of Islamic world doing by Western media which focused mainly on the issues of terrorism, intolerance, poverty, conflicts, fanaticism, horrible disease, low life qualities among Islamic countries, backwardness and lack of progress. This article explores and describes some statements made by Western media (as well as Western journalists), along with events as the setting of such comments. In order to overcome such situations, media monitoring must be professional and constant. Those who concern with the misleading information toward Islam must provide clear, short, and well-written press releases at regular intervals. Another suggestion is by drawing attention of ethnic youth toward journalism as noble profession and good trade.